Effect of dietary supplementation of astxanthin, prill fat and their combination on antioxidants and immunity status of lactating buffaloes during heat stress - Somagond, Yallappa Mallappa; Singh, Sohan Vir; Deshpande, Aditya; Sheoran, Parvender; Chahal, Ved Parkash (Buffalo Bulletin, 2021)
To evaluate the role of dietary supplementation of astaxanthin, prill fat and their combination on antioxidants and immune status of lactating buffaloes during heat stress. Twenty four lactating buffaloes (first to fourth parity) were selected and divided equally into four groups i.e. Group I (control), Group II (astaxanthin 0.25 mg/kg body wt/day), Group III (prill fat 100 g/animal/day) and Group IV (astaxanthin + prill fat). Plasma was separated from the blood collected at fortnightly interval for the analysis of antioxidant enzymes and interleukins levels. The levels of superoxide dismutase and catalase were significantly lower in astaxanthin supplemented groups (Group II and Group IV) compared to Group I and Group III. The levels of pro-inflammatory cytokine (Interleukin -2) was significantly (P<0.05) lower in astaxanthin supplemented groups (Group II and Group IV) compared to Group I whereas levels of anti-inflammatory cytokines (Interleukin -10) was significantly (P<0.05) higher in all supplemented groups (Group II, Group III and Group IV) than Group I. Results showed that, dietary supplementation of astaxanthin (potent antioxidant) was able to alleviate the heat stress induced changes by lowering the levels of antioxidant enzymes (SOD and CAT) and pro-inflammatory cytokine (IL-2) and improving the levels of anti-inflammatory (IL-10) cytokines in lactating buffaloes during summer season.